PENGARUH PENAMBAHAN ANTIOKSIDAN TERHADAP KUALITAS SEMEN CAIR DOMBA LOKAL UMUR PUBERTAS - Nurcholidah Solihati; Siti Darodjah Rasad; Tuti Kustini (Fakultas Peternakan, Universitas Padjadjaran, 2020)
The aims of the research was to determine the effect of antioxidants addition on liquid semen quality of young ram and knowing which antioxidants have the most excellent effect. The research was conducted experimentally with completely randomized design (CRD). There were three treatments, that were P0 = semen added diluent without the addition of antioxidants as a control, P1 = semen added diluent have been added 9,3 mM glutathione, P2 = semen added diluent have been added 9,3 mM alpha tocopherol. Each treatment was repeated six times. The parameters consist of sperm motility and intact plasma membrane (IPM). The result showed that the addition of antioxidants can maintain liquid semen motility of young ram on day 6, 9, and 11, while addition of antioxidant has no significant effect on IPM. Result showed that glutathion is the best antioxidants that can maintain motility on day 6, 9 and 11 is glutathione with the average 72,28%, 62,47%, and 54,43%, nevertheless for alpha tocopherol with average 58,11%, 48,13%, and 41,95% gave result is not significant to P0 motility with average 62,29%, 53,08%, and 42,36%. It is concluded that addition of antioxidant can maintain liquid semen motility on day 6, 9, and 11 but can not give effect to the IPM, and the addition of antioxidant glutathione give the most excellent effect to liquid semen motility.